The essence of a human being and "otherworldly": ethical and metaphysical views - A. Y. Morozov, (Ukrainian Cultural Studies, 2019)
The article shows that the elimination of the metaphysical concepts of "essence", "nature", "transcendental" makes it impossible for a person to set apart the poles of "being" and "due". And therefore it makes impossible the ethics itself. The metaphysical apriorism can justify the latter. The approaches of positivism and historicism in the moral sciences both destroy the tradition of natural law, undermines the theoretical foundation of democracy and European universalism. It is noted that the basis for the disclosure of the essence of human is participation in the otherworldly realm (G. Hegel). In the experience of the latter, the transcendence of the daily mode of being, the rise of natural existence to the level of "supernatural" occurs. The otherworldly comes in two versions: the strong version of the non-world is the sacred mystery of the divine, and the weak one is the romanticized space of a fairy tale. The fairy serves as a substitute for the sacred in the post-enlightenment era and performs therapeutic and preventive functions in the treatment of the moral diseases of our time – cynical mind, individualism, relativism, cult of consumption. It is noted that the absence of the otherworldly as a meta-value in the cultural space of a modern secular person leads to the fall of the natural (essentially human) mode of existence to an unnatural level, in a state of dehumanization.
Keywords: metaphysics, universal values, essence, otherworldly, everyday life, sacred, fairy, cynical mind, authenticity, dehumanization